Connection Formula for the Jackson Integral of Type An and Elliptic Lagrange Interpolation - Ito, M.; Noumi, M. (Symmetry, Integrability and Geometry: Methods and Applications, 2018)
We investigate the connection problem for the Jackson integral of type An. Our connection formula implies a Slater-type expansion of a bilateral multiple basic hypergeometric series as a linear combination of several specific multiple series. Introducing certain elliptic Lagrange interpolation functions, we determine the explicit form of the connection coefficients. We also use basic properties of the interpolation functions to establish an explicit determinant formula for a fundamental solution matrix of the associated system of q-difference equations.